2018
DOI: 10.1097/cej.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Height and risk of colorectal cancer: a meta-analysis

Abstract: Several epidemiological studies have investigated the relationship between height and risk of colorectal cancer (CRC), but the results were inconsistent. Thus, a meta-analysis of observational studies was carried out to clarify this association. A literature search was performed in PubMed and Web of Science databases for all relevant studies up to 25 May 2016. The random-effects model was used to calculate the pooled relative risks (RRs) and restricted cubic spline model was adopted for the dose-response analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…A global meta-analysis reported that each 5-cm increase in height was associated with a RR of 1.04-fold in Western countries [13], and this positive association was also supported by a recent global review [62]. Some Asian research supported this conclusion.…”
Section: Non-modifiable Factorsmentioning
confidence: 73%
“…A global meta-analysis reported that each 5-cm increase in height was associated with a RR of 1.04-fold in Western countries [13], and this positive association was also supported by a recent global review [62]. Some Asian research supported this conclusion.…”
Section: Non-modifiable Factorsmentioning
confidence: 73%
“…These trends are not restricted only to the Asian region. A global meta-analysis obtains a relative risk of 1.25 (1.18-1.32) for CRC with the highest vs lowest height[ 34 ]. Likewise, a prospective systematic review corroborates the idea where CRC’s risk multiply by 1.06 for every 5 kg/m 2 increase in BMI[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Models were adjusted for age (continuous; years), height (continuous; cm) [ 25 ], family history of cancer (yes, no), educational level (categorical; low, medium, and high), smoking (continuous; pack/year), BMI (continuous; kg/m 2 , [ 26 ]), physical activity (continuous; leisure [i.e. cycling, dancing], household [i.e.…”
Section: Methodsmentioning
confidence: 99%